Pendekatan Inovatif Guru dalam Menghidupkan Pembelajaran Batik melalui Pameran di Sekolah Bina Bangsa Malang - Oktaviani, Puteri Anisah; Prasetyo, Abdul Rahman (Mahesa Research Center, 2025)
Learning strategies are plans designed by teachers to achieve learning goals effectively and efficiently. In learning Fine Arts, especially batik material, teachers at the Bina Bangsa School in Malang apply innovative approaches so that students can understand the material in depth. This research aims to describe teachers' teaching strategies in using the Cambridge Curriculum, explain the challenges faced in craft learning, and describe teachers' strategies for overcoming these challenges. This research uses a descriptive qualitative method with a Creswell case study approach, which includes biographical and ethnographic stages, case studies, theory and phenomenology. The research results show that the methods used by teachers such as direct demonstrations, direct practice, and collaborative projects are proven to be able to build students' in-depth understanding of the process and value of batik art. In conclusion, this innovative strategy supports the achievement of Fine Arts learning objectives, especially batik material, with a creative, flexible and effective approach in building students' understanding of the history of batik and teaching traditional arts in a way that is relevant and attractive to the younger generation. This can be seen in the work that has been created by students which is used on certain days and the good work is exhibited in direct collaboration with external parties.